Analisis Waktu dan Biaya Perbandingan Erection Steel Box Girder Menggunakan Metode Skid Launching dan Launcher - Prakoso, Catur; Azhar, Moh (Jurnal Ilmiah Rekayasa Sipil, 2024)
This research was conducted on the construction project of Cimanggis - Cibitung toll road section 2 Sta. 27+070 to Sta. 50+353. The background of this research is the need to know a more efficient implementation method in terms of time and cost, given the importance of effectiveness and efficiency in construction projects. The purpose of this research is to determine the time of girder erection work using the skid launching method and the girder launcher method, Knowing the cost of implementing girder erection work with both methods, Comparing the efficiency of time and cost between the skid launching method and the girder launcher method, The data that has been obtained is analysed. From the results of the analysis of the two tools obtained the results of the erection process, namely the Launcher girder method is more efficient in the time of erection of steel box girder, requiring 6356 minutes compared to 7500 minutes in the Skid Launching method, the data obtained in terms of time while in terms of cost the Launcher girder method is more economical with a cost of Rp 13,867,349 per span compared to Rp 35,767,019 in the Skid Launching method. resulting in cost savings of IDR 21,899,669 or around 39%.From the data obtained, we can determine the most efficient method in terms of time and cost between the two methods. The methodology used in this study includes primary and secondary data collection, analysis of material requirements, productivity and duration of work, and cost analysis. The results showed that the girder launcher method is more efficient in terms of time and cheaper in terms of cost compared to the skid launching method. The findings are expected to serve as a reference in the implementation of similar projects in the future.